2011
DOI: 10.1161/circinterventions.110.959262
|View full text |Cite
|
Sign up to set email alerts
|

Procedure-Type Risk Categories for Pediatric and Congenital Cardiac Catheterization

Abstract: Background— The Congenital Cardiac Catheterization Project on Outcomes (C3PO) was established to develop outcome assessment methods for pediatric catheterization. Methods and Results— Six sites have been recording demographic, procedural and immediate outcome data on all cases, using a web-based system since February 2007. A sample of data was independently audited for validity and data completeness. In 2006, participants categorized 84 procedure types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
2
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 111 publications
(125 citation statements)
references
References 8 publications
3
105
2
3
Order By: Relevance
“…This is contrary to previous studies that only list death, stroke, or device erosion as major complications. Though the Bergersen et al study does include a comprehensive listing of complications, it does not stratify patients and the complications according to patient size (7,17). In 1 study of 52 patients, the investigators reported no major complications, yet discussed 2 device embolizations that were classified as minor complications (6).…”
Section: Discussionmentioning
confidence: 99%
“…This is contrary to previous studies that only list death, stroke, or device erosion as major complications. Though the Bergersen et al study does include a comprehensive listing of complications, it does not stratify patients and the complications according to patient size (7,17). In 1 study of 52 patients, the investigators reported no major complications, yet discussed 2 device embolizations that were classified as minor complications (6).…”
Section: Discussionmentioning
confidence: 99%
“…A full description of procedure-type risk group development has been previously described in detail. 10 In brief, the procedure-type risk groups were created using data from the Congenital Cardiac Catheterization Project on Outcomes (C3PO) and were developed based on both expert consensus and empirically derived data. Four categories of procedural risk were created (Category 1= procedures associated with lowest risk vs. Category 4=procedures associated with highest risk).…”
Section: Methodsmentioning
confidence: 99%
“…10,13 Categories were developed by using expert judgment and empirical methods in a derivation cohort and validated in a prospective cohort in the Congenital Cardiac Catheterization Project on Outcomes database. A case is assigned to 1 category based on the characteristics of the case; for diagnostic procedures the cases are stratified by age group.…”
Section: Risk Categorymentioning
confidence: 99%